Numerical simulation of the dead-volume effect in seismic-frequency measurements of elastic properties of fluid-saturated rocks. Issue 1 (1st December 2019) - Cao, Cheng-Hao; Gurevich, Boris; Mikhaltsevitch, Vassili; Fu, Li-Yun
Summary: Low-frequency measurements of the elastic properties rocks based on the forced-oscillation method is an emerging approach for calibration of well log and seismic measurements. The dispersive properties observed in the low-frequency experiments are usually dependent on the boundary conditions of a tested rock sample, whether the sample surface is properly sealed, or surrounded by rigid pore-fluid containers connected with the pore space of the rock, so-called "dead volumes". By treating the dead volume as a specific porous material, we analysed the impact of the dead volumes on the strains in the sample via numerical simulation of the forced oscillation tests, our simulation is based on the models incorporating the properties and physical characteristics of the laboratory samples. The numerical results are in good agreement with the analytical solutions.